Agro-Morphological Characterization and Diversity Assessment of Rice Landraces in Nepal (Agriculture Development Journal, 2022)
Plant genetic resources are raw materials and their use in breeding is one of the most sustainable ways to conserve agro-biodiversity. Field research was conducted at National Agriculture Genetic Resources Centre (NAGRC) during 2018 & 2019 with the objective of agro-morphological characterization and diversity assessment of rice landraces. Forty-two landraces collected from 21 districts of Nepal were characterized and evaluated by using non replicated row design. The phenotypic diversity was assessed based on fourteen qualitative and thirteen quantitative characters following the descriptors developed by Bioversity International, IRRI and WARDA. Basic statistics were calculated by using Excel 2016 and UPGMA clustering and PCA was done with MINITAB-17. The diversity index (H') and coefficient of variation for different traits ranged from 0.16-0.96 and 8.00-47.77 respectively. Clustering grouped the landraces into four clusters with minimum similarity level of 46.33%. Landraces of cluster three i.e. NGRC01917, NGRC03034, NGRC03395, NGRC03057, NGRC03163 are found to be superior in terms of maturity days and yield. PCA partitioned the total variation into three principal components contributing 75.5% of the cumulative variance. Thus, the present study is the preliminary picture for characterization and diversity analysis in Nepalese rice landraces that can be used by the breeder in rice improvement program.